Creativity and (global, ethnic, host) cultural identifications: An examination in migrant and host national samples - Soler Pastor, Elia; Bobowik, Magdalena; Benet Martínez, Verónica (Frontiers in Psychology, 2022)
We live in an era of unprecedented interconnectivity and challenges (e.g., climate change, pandemics) that require global mindsets and creative approaches. While research on global identification has increased in recent years, the question of whether it can facilitate creativity remains largely unexplored. Moreover, despite the evidence linking multicultural experiences and global identities, migrant populations have been overly underrepresented in this area of research. We examine the association between global culture identification and creativity in the Alternate Uses Test (Guilford, 1967), across two different samples residing in Spain: a host national and majorly student sample (N = 326) and a culturally diverse immigrant sample (N = 122). Additionally, we test the predictive value of ethnic identification (in both samples) and host culture identification (in the immigrant sample). Regression analyses reveal that global culture identification positively predicts creativity among host national participants, and host culture identification predicts creativity among immigrant participants. Our results suggest that developing a cultural identity that transcends the one acquired through enculturation (i.e., global culture identification for the host national sample, host culture identification for the immigrant sample) has the potential of facilitating creative behavior.